1996
DOI: 10.1346/ccmn.1996.0440603
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Lead(II) and Chromium(III) Reaction Products on Phyllosilicate Surfaces As Determined By Atomic Force Microscopy

Abstract: Abstract--Redox and acid-base reactions play important roles in the fate of metal contaminants in soils and sediments. The presence of significant amounts of Cr, Pb and other toxic heavy metals in contaminated soils and sediments is of great environmental concern. Oxidation states and dissolution characteristics of the heavy metals can exert negative effects on the natural environment. Atomic force microscopy (AFM) was used to follow the changes in morphology and structure of reaction products of Cr and Pb for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Fe(II) is found in many silicates, and oxidation-reduction reactions between aqueous species and structurally bound Fe on or beneath the surface of both silicates and oxides can control the redox state of associated solutes. In particular, studies have demonstrated the heterogeneous reduction of Cr(VI) by Fe(II) in biotite, vermiculite, illite, smectites, chlorite, magnetite, ilmenite, Fe(II)-hematite, Fe(II)-goethite, and sulfides (Eary and Rai, 1989;Ilton and Veblen, 1994;Gan et al, 1996;White and Peterson, 1996;Patterson et al, 1997). However, it is not known if this mechanism is active at alkaline pH, and it is not clear what role, if any, host mineral dissolution has on Cr transport and fate.…”
Section: Introductionmentioning
confidence: 99%
“…Fe(II) is found in many silicates, and oxidation-reduction reactions between aqueous species and structurally bound Fe on or beneath the surface of both silicates and oxides can control the redox state of associated solutes. In particular, studies have demonstrated the heterogeneous reduction of Cr(VI) by Fe(II) in biotite, vermiculite, illite, smectites, chlorite, magnetite, ilmenite, Fe(II)-hematite, Fe(II)-goethite, and sulfides (Eary and Rai, 1989;Ilton and Veblen, 1994;Gan et al, 1996;White and Peterson, 1996;Patterson et al, 1997). However, it is not known if this mechanism is active at alkaline pH, and it is not clear what role, if any, host mineral dissolution has on Cr transport and fate.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas organic matter may be a primary source for Cr(VI) reduction in soils (Bartlett and Kimble, 1976), Fe(II)-containing minerals are more important for Cr(VI) reduction in subsurface formations (Eary and Rai, 1991;Anderson et al, 1994;Kent et al, 1994). Gan et al (1996) demonstrated that the reduction of structural Fe(II) increased the Cr(VI) removal efficiency of clays.…”
Section: Introductionmentioning
confidence: 99%
“…With X-ray photoelectron spectrosco- Ilton and Veblen (1994) demonstrated the coupled sorption and reduction of chromate at the biotite/water interface. Using atomic force microscopy (AFM), Gan et al (1996) showed that Cr(VI) directly reacted with an Fe(II)-containing smectite, forming precipitates on the smectite surface. Gan et al (1996) also found chromium oxide in Cr(VI)-treated smectite SWa-1, based on an infrared vibration at 540 cm -~ that is assigned to a Cr-O lattice vibration (Amonette and Rai, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe(II)-containing minerals are more important for Cr(VI) reduction in subsurface formations (Eary and Rai, 1991;Anderson et al, 1994;Kent, et al, 1994). The reduction of structural Fe(II) is known to increase the Cr(VI) removal efficiency of clays (Gan et al, 1996). Earlier studies of Cr(VI) reduction by Fe(II)-containing minerals suggested that the minerals must dissolve to release Fe(II) into solution before reduction could occur.…”
Section: (B) Reduction Of Cr(vi) By Inorganic and Organic Colloidsmentioning
confidence: 99%